Analisis komparatif perlakuan akuntansi penyusutan aset tetap peralatan kantor menurut perusahaan dan sak etap bab 15 menggunakan metode garis lurus - Muhammad Indra Irawan; Cornelius Rantelangi; Raden Priyo Utomo (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
This study aimed to compare the presentation of fixed assets include office equipment Financial Accounting Standards Entities Without Public Accountability and according to the Company. The tools used in this study are SAK ETAP BAB 15 as a standard that has been set in the accounting of fixed assets.  Where the total amount of fixed assets depreciation of office equipment in 2015 according to Blessing CV Ananda in Samarinda is Rp 60,212,360.00 accumulated depreciation of Rp 164,175,530.00, while the overall number according to the Financial Accounting Standards Entities Without Public Accountability (ETAP) depreciation of office equipment amounting Rp59.833.089,03 accumulated depreciation of Rp 163,796,259.03. From the analysis there is a difference between the calculation of depreciation according to Blessing CV Ananda with Financial Accounting Standards Entities Without Public Accountability (ETAP), for depreciation of Rp 379,270.97 and accumulated depreciation of Rp 379,270.97. So it made adjusting entries to fixed assets owned office equipment Blessings CV Ananda in Samarinda.